Greening the Workforce: Exploring HRM Practices, Employee Mediators, and Environmental Performance in the Manufacturing Industry - Naqvi, Seyda Taram Abbas; Shaikh, Omar Ahmed; Iqbal, Asim (Journal of Development and Social Sciences, 2025)
This study Examines whether GHRM—green recruitment, green performance management, and green rewards—predicts green environmental performance (GEP) in Pakistani manufacturing, testing employee commitment (EC) and employee attitude (EA) as mediators; scope: Karachi manufacturing employees and their firms. Environmental performance depends on embedding sustainability in HR systems. Social Exchange Theory suggests valued green practices elicit reciprocal mindsets and behaviors that strengthen outcomes. Pakistan-specific evidence on multi-lever GHRM via commitment and attitudes remains limited. Positivist, deductive, cross-sectional survey of 400 Karachi manufacturing employees (stratified random). Validated, adapted scales; PLS-SEM (SmartPLS 4) assesses the reflective measurement model and tests direct/indirect paths via EC and EA. Ethical safeguards and anonymity are ensured.Green rewards show a strong positive direct effect on GEP. Green recruitment and green performance management display weaker direct but significant mediated effects. EC and EA are significant mediators; the model demonstrates sound reliability/validity and meaningful explanatory power. Prioritize coherent green rewards, align recruitment and performance criteria with sustainability, and build EC/EA through training, participation, and visible leadership to convert GHRM into durable environmental gains.